An IOT Based Detection Model for the Level of Autism in a Context-Aware Health Care - Pradhan, Sipali; Das, Surajit; Nayak, Samaleswari Prasad; Mantri, J.K (International Journal of Computer Sciences and Engineering, 2025)
Autism Spectrum Disorder (ASD) or simply Autism a progression of deep-rooted neuron developmental issue which is basically a brain development disorder found in the kids when they are around eighteen months. The kids suffer from communication, social interaction and repetitive behavior problems and are very difficult to identify autism on a proper way. If Autism is remained undetected in children within the age of 1 to 3 years from birth there are chances of regeneration of the symptoms manifested by the autism in the adult stage which is generally noted to be after or around the age of 60 years. Through our paper, we have proposed an IoT based detection model to get data for five symptoms using different sensors and can be transferred to the destination machine for testing using the internet from a remote location. The goal of this paper is to review the Autism Spectrum Disorder problem by generating some IF-THEN rules and build a system to identify the level of Autism using Adaptive Neuro-Fuzzy Inference System (ANFIS).